Skeletal muscle metabolism and contraction performance regulation by teneurin C-terminal-associated peptide-1 - Hogg, David W.; Reid, Andrea L.; Dodsworth, Thomas L.; Chen, Yani; Reid, Ross M.; Xu, Mei; Husic, Mia; Biga, Peggy R.; Slee, Andrew; Buck, Leslie T.; Barsyte-Lovejoy, Dalia; Locke, Marius; et al. (Frontiers in Physiology, 2022)
Skeletal muscle regulation is responsible for voluntary muscular movement in vertebrates. The genes of two essential proteins, teneurins and latrophilins (LPHN), evolving in ancestors of multicellular animals form a ligand-receptor pair, and are now shown to be required for skeletal muscle function. Teneurins possess a bioactive peptide, termed the teneurin C-terminal associated peptide (TCAP) that interacts with the LPHNs to regulate skeletal muscle contractility strength and fatigue by an insulin-independent glucose importation mechanism in rats. CRISPR-based knockouts and siRNA-associated knockdowns of LPHN-1 and-3 in the C2C12 mouse skeletal cell line shows that TCAP stimulates an LPHN-dependent cytosolic Ca2+ signal transduction cascade to increase energy metabolism and enhance skeletal muscle function via increases in type-1 oxidative fiber formation and reduce the fatigue response. Thus, the teneurin/TCAP-LPHN system is presented as a novel mechanism that regulates the energy requirements and performance of skeletal muscle.